Cordyceps militaris fruit body extract ameliorates membranous glomerulonephritis by attenuating oxidative stress and renal inflammation via the NF-κB pathway. Issue 4 (23rd March 2016) - Song, Jingjing; Wang, Yingwu; Liu, Chungang; Huang, Yan; He, Liying; Cai, Xueying; Lu, Jiahui; Liu, Yan; Wang, Di
Abstract : Membranous glomerulonephritis (MGN) is a common pathogenesis of nephritic syndrome in adult patients. Abstract : Membranous glomerulonephritis (MGN) is a common pathogenesis of nephritic syndrome in adult patients. Nuclear factor kappa B (NF-κB) serves as the main transcription factor for the inflammatory response mediated nephropathy. Cordyceps militaris, containing various pharmacological components, has been used as a kind of crude drug and folk tonic food for improving immunity and reducing inflammation. The current study aims to investigate the renoprotective activity of Cordyceps militaris aqueous extract (CM) in the cationic bovine serum albumin (C-BSA)-induced rat model of membranous glomerulonephritis. Significant renal dysfunction was observed in MGN rats; comparatively, 4-week CM administration strongly decreased the levels of 24 h urine protein, total cholesterol, triglyceride, blood urea nitrogen and serum creatinine, and increased the levels of serum albumin and total serum protein. Strikingly, recovery of the kidney histological architecture was noted in CM-treated MGN rats. A significant improvement in the glutathione peroxidase and superoxide dismutase levels, and a reduced malondialdehyde concentration were observed in the serum and kidney of CM-treated rats. Altered levels of inflammatory cytokines including interleukins, monocyte chemoattractant protein-1, intercellular adhesion molecule 1, vascular adhesion molecule 1, tumor necrosis factor-α, 6-keto-prostaglandin F1α, and nuclear transcriptional factor subunit NF-κB p65 reverted to normal levels upon treatment with CM. The present data suggest that CM protects rats against membranous glomerulonephritis via the normalization of NF-κB activity, thereby inhibiting oxidative damage and reducing inflammatory cytokine levels, which further provide experimental evidence in support of the clinical use of CM as an effective renoprotective agent.